BF3.SiO2 Nanoparticles: A Solid Phase Acidic Catalyst for Efficient One-pot Hantzsch Synthesis of 1, 4-dihydropyridines. (January 2013) - Sadeghi, Bahareh; Namakkoubi, Ashraf; Hassanabadi, Alireza
The solvent-free Hantzsch reaction between ethyl acetoacetate or 1, 3-indandione, an aromatic aldehyde and ammonium acetate catalysed by BF3 .SiO2 nanoparticles provided an efficient one-step synthesis of 1, 4-dihydropyridines in excellent yields.